2013
DOI: 10.1093/bja/aes594
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of tidal volume from four anaesthesia ventilators during volume-controlled ventilation: a bench study

Abstract: Under experimental conditions, the volume error differed significantly between the four new anaesthesia ventilators tested and was influenced by FGF, although this effect may not be clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
2
22
0
2
Order By: Relevance
“…We found several studies with the same resistance parameters, 2,8,14,15 compliance, 2 and tidal volume (V T ) 2,8,[14][15][16][17] as in our study. Here again, there is no formal scientific evidence that the parameters presented by Mr Chatburn are more "realistic.…”
Section: Choice Of Parameterssupporting
confidence: 69%
See 1 more Smart Citation
“…We found several studies with the same resistance parameters, 2,8,14,15 compliance, 2 and tidal volume (V T ) 2,8,[14][15][16][17] as in our study. Here again, there is no formal scientific evidence that the parameters presented by Mr Chatburn are more "realistic.…”
Section: Choice Of Parameterssupporting
confidence: 69%
“…It is an extreme functioning of the ventilator, but it was tested in older studies. 2,8,[14][15][16] It is interesting to us to know what a transport ventilator can do or not do in extreme conditions.…”
Section: Choice Of Parametersmentioning
confidence: 99%
“…Therefore, we implemented the same experiment as that performed in an older study (10 y ago) 2 using the same parameters for the static portion; used the same dynamic experiments as used in many previous bench studies. [3][4][5][6][7][8] In addition, we showed that the most recent turbine transport ventilators are a breakthrough in the field of transport ventilators even if they have some limitations, and their performances are close to those of ICU ventilators.…”
Section: Simulation Studies For Device Evaluation-replymentioning
confidence: 67%
“…Most of the studies reporting ventilator performance 3,4 use some version of the Training and Test Lung (TTL) simulator (Michigan Instruments, Grand Rapids, Michigan). This device has one or two spring-loaded bellows to model compliance (adjustable spring tension varies compliance values) connected in series with parabolic flow resistors.…”
Section: Simulation For Ventilator Performance Studiesmentioning
confidence: 99%
“…Sisteme razdruževanja svežih plinov vsebujejo naslednje anestezijske delovne postaje: Dräger Fabius GS, Dräger Narkomed 6000, Dräger Narkomed 6400, Dräger Primus, Dräger Apollo, Dräger Zeus in Datascope Anestar (22,24).…”
Section: Dihalni Balon In Mehanično Predihavanjeunclassified